C-KIT EXPRESSION IN VARIOUS DEGREES OF HISTOPATHOLOGY DIFFERENTIATION OF RETINOBLASTOMA IN MOHAMMAD HOESIN HOSPITAL PALEMBANG - Rusdianto Rusdianto; Keisha Devita Primananda (Majalah Kedokteran Sriwijaya, 2020)
Retinoblastoma is a malignant intraocular neoplasm in pediatric which composed of embyonic tumour cells from retinoblasts of neuroepithelial origin with a relative incidence of 3% of all pediatric tumours. Histopathology examination can confirmed the diagnosis of retinoblastoma. Immunohistochemical staining with C-kit antibody can be used to identify the expression of C-kit in paraffin block of retinoblastoma sample.This study was conducted to identify C-kit expresion in various degrees of histopathology differentiation’s retinoblastoma in Mohammad Hoesin Hospital Palembang.. A descriptive study used on the paraffin blocks of 19 cases retinoblastoma in RSUP dr. Mohammad Hoesin from January 2012- July 2017. The degree of histopathologic differentiation and invasion of retinoblastoma was investigated by Hematoksilin-Eosin stain, and the C-kit expression stained by immunohistochemistry using antibody C-kit ready to use. Data was being presented in tabular form to identify C-kit expression. Retinoblastoma which expressed C-kit in this study are 63,16% among all sample. C-kit expressions were detected in 25% well differentiated, 50 % moderately differentiated, and 25% poorly differentiated of histopathological differentiation degree, also in 50% sample with optic nerve invasion and 58,33% in scleral invasion. C-kit expression was negative in 36,84% sample. In this study, C-kit expression was found more than half in retinoblastoma sample.